Effects of anonymous peer observation on adolescents' preference for immediate rewards. Issue 1 (6th November 2013) - Weigard, Alexander; Chein, Jason; Albert, Dustin; Smith, Ashley; Steinberg, Laurence
Abstract Research suggests that the presence of peers influences adolescent risk‐taking by increasing the perceived reward value of risky decisions. While prior work has involved observation of participants by their friends, the current study examined whether observation by an anonymous peer could elicit similarly increased reward sensitivity. Late adolescent participants completed a delay discounting task either alone or under the belief that performance was being observed from a neighboring room by an unknown viewer of the same gender and age. Even in this limited social context, participants demonstrated a significantly increased preference for smaller, immediate rewards when they believed that they were being watched. This outcome challenges several intuitive accounts of the peer effect on adolescent risk‐taking, and indicates that the peer influence on reward sensitivity during late adolescence is not dependent on familiarity with the observer. The findings have both theoretical and practical implications for our understanding of social influences on adolescents' risky behavior.